2008
DOI: 10.1155/2008/174202
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone-Induced Perforation of the Common Bile Duct in Pregnancy

Abstract: Spontaneous perforation of the extrahepatic biliary system is a rare presentation of ductal stones. We report the case of a twenty-year-old woman presenting at term with biliary peritonitis caused by common bile duct (CBD) perforation due to an impacted stone in the distal common bile duct. The patient had suffered a single herald episode of acute gallstone pancreatitis during the third trimester. The patient underwent an emergency laparotomy, bile duct exploration, and removal of the ductal stone. The postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“… [ 11 ] Goodlin et al 1991 ? 4 Gall bladder Gangrene of Gall bladder Postpartum Cholecystectomy [ 12 ] Petrozza et al 1995 28 G7P6 23 G4P4 2 Gall bladder Gall stone Postpartum Cholecystectomy [ 13 ] McGrath et al 2005 34 G1P0 1 CBD Gall stone Postpartum Sphincterotomy + Stent placement [ 14 ] Talwar et al 2006 28 G2P1 1 Gall bladder Gall stone During pregnancy Cholecystectomy [ 15 ] Talwar et al 2006 21 G1P0 1 CBD Idiopathic During pregnancy Over T-tube repair [ 15 ] Dabbas et al 2008 20 G1P1 1 CBD Gall stone Postpartum Choledocholithotomy + Over T-Tube repair [ 16 ] Bediako-Bowan et al 2013 29 ? 1 CBD Idiopathic …”
Section: Discussionmentioning
confidence: 99%
“… [ 11 ] Goodlin et al 1991 ? 4 Gall bladder Gangrene of Gall bladder Postpartum Cholecystectomy [ 12 ] Petrozza et al 1995 28 G7P6 23 G4P4 2 Gall bladder Gall stone Postpartum Cholecystectomy [ 13 ] McGrath et al 2005 34 G1P0 1 CBD Gall stone Postpartum Sphincterotomy + Stent placement [ 14 ] Talwar et al 2006 28 G2P1 1 Gall bladder Gall stone During pregnancy Cholecystectomy [ 15 ] Talwar et al 2006 21 G1P0 1 CBD Idiopathic During pregnancy Over T-tube repair [ 15 ] Dabbas et al 2008 20 G1P1 1 CBD Gall stone Postpartum Choledocholithotomy + Over T-Tube repair [ 16 ] Bediako-Bowan et al 2013 29 ? 1 CBD Idiopathic …”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the authors reported that the loss of bile duct wall continuity on CT and high bilirubin levels in ascites were important diagnostic factors [ 4 , 16 , 23 , 24 ]. Although most of the other cases were diagnosed by exploratory laparotomy, the perforation site in some cases could not be identified intraoperatively and required subsequent re-operation [ 5 ] or endoscopic retrograde cholangiopancreatography [ 3 ] for diagnosis. Notably, in a few cases, the perforation site could not be identified intraoperatively despite bile duct perforation being suspected preoperatively [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common site of extrahepatic bile duct perforation (excluding the gallbladder which complicates up to 10% cases of acute cholecystitis [ 2 ]) is the CBD (42 patients) followed by the common hepatic duct (28 patients) [ [6] , [11] ]. In one case series, nine of the 11 patients had intrahepatic ductal perforation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%